(untitled) (Global Journals of Research in Engineering, 2023)
Piezoresistive pressure sensors are manufactured frequently by the researcher around the world currently The most of the sensors are passive in nature The yarns may be intrinsically conductive i e stainless steel yarn or it may be made conductive by coating i e graphene oxide coated polyester yarn The stainless steel yarn is embroidered in the fabric When installed inside a garment the sensors can track both muscle activity and vital signs in people The polyester fabric that dip-coated with graphene oxide GO has a wide detection range and good sensitivity making it suitable for use as a pressure sensor in plantar measurement and gait-analysis applications